Evolution of ancient satellite DNAs in extant alligators and caimans (Crocodylia, Reptilia) - Sales-Oliveira, Vanessa C.; dos Santos, Rodrigo Zeni [UNESP]; Goes, Caio Augusto Gomes [UNESP]; Calegari, Rodrigo Milan [UNESP]; Garrido-Ramos, Manuel A.; Altmanová, Marie; Ezaz, Tariq; Liehr, Thomas; Porto-Foresti, Fabio [UNESP]; Utsunomia, Ricardo [UNESP]; Cioffi, Marcelo B. (Springer Nature, 2024)
Background: Crocodilians are one of the oldest extant vertebrate lineages, exhibiting a combination of evolutionary success and morphological resilience that has persisted throughout the history of life on Earth. This ability to endure over such a long geological time span is of great evolutionary importance. Here, we have utilized the combination of genomic and chromosomal data to identify and compare the full catalogs of satellite DNA families (satDNAs, i.e., the satellitomes) of 5 out of the 8 extant Alligatoridae species. As crocodilian genomes reveal ancestral patterns of evolution, by employing this multispecies data collection, we can investigate and assess how satDNA families evolve over time. Results: Alligators and caimans displayed a small number of satDNA families, ranging from 3 to 13 satDNAs in A. sinensis and C. latirostris, respectively. Together with little variation both within and between species it highlighted long-term conservation of satDNA elements throughout evolution. Furthermore, we traced the origin of the ancestral forms of all satDNAs belonging to the common ancestor of Caimaninae and Alligatorinae. Fluorescence in situ experiments showed distinct hybridization patterns for identical orthologous satDNAs, indicating their dynamic genomic placement. Conclusions: Alligators and caimans possess one of the smallest satDNA libraries ever reported, comprising only four sets of satDNAs that are shared by all species. Besides, our findings indicated limited intraspecific variation in satellite DNA, suggesting that the majority of new satellite sequences likely evolved from pre-existing ones.
Keywords: Library hypothesis; Repetitive DNA; Reptiles